2011
DOI: 10.1371/journal.pone.0025778
|View full text |Cite
|
Sign up to set email alerts
|

Genotypic and Phenotypic Properties of Cattle-Associated Campylobacter and Their Implications to Public Health in the USA

Abstract: Since cattle are a major source of food and the cattle industry engages people from farms to processing plants and meat markets, it is conceivable that beef-products contaminated with Campylobacter spp. would pose a significant public health concern. To better understand the epidemiology of cattle-associated Campylobacter spp. in the USA, we characterized the prevalence, genotypic and phenotypic properties of these pathogens. Campylobacter were detected in 181 (19.2%) out of 944 fecal samples. Specifically, 71… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
36
1

Year Published

2012
2012
2020
2020

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 41 publications
(42 citation statements)
references
References 44 publications
(67 reference statements)
5
36
1
Order By: Relevance
“…This is consistent with published sequence types of C. jejuni originating in the western United States, where ST-982 originated primarily from cattle or other ruminants (http: //pubmlst.org/campylobacter). ST-42 complex and ST-61 complex isolates from cattle in our study were also consistent with reports of cattle-origin C. jejuni from other regions of the United States (33). Multiple molecular genotyping studies have found that Campylobacter isolates from bovine and human hosts frequently have the same genotype by a variety of methods, including pulsed-field gel electrophoresis (PFGE), randomly amplified polymorphic DNA (RAPD) typing, flagellin gene typing, and MLST (35)(36)(37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…This is consistent with published sequence types of C. jejuni originating in the western United States, where ST-982 originated primarily from cattle or other ruminants (http: //pubmlst.org/campylobacter). ST-42 complex and ST-61 complex isolates from cattle in our study were also consistent with reports of cattle-origin C. jejuni from other regions of the United States (33). Multiple molecular genotyping studies have found that Campylobacter isolates from bovine and human hosts frequently have the same genotype by a variety of methods, including pulsed-field gel electrophoresis (PFGE), randomly amplified polymorphic DNA (RAPD) typing, flagellin gene typing, and MLST (35)(36)(37)(38)(39)(40).…”
Section: Discussionsupporting
confidence: 92%
“…This clonal complex is reported frequently for humans, cattle, and poultry in diverse geographic locations (32)(33)(34). The most frequent ST within the ST-21 complex was ST-982, which included 7 human isolates and 6 bovine isolates.…”
Section: Discussionmentioning
confidence: 99%
“…After incubation, 100 lL of culture was spread onto a modified charcoal cefoperazone deoxycholate agar (mCCDA) plate (CM 0739, Oxoid) containing the selective supplement (SR155E, Oxoid) and incubated for 48 h at 42°C microaerobically (Engberg et al, 2000). Where available, three presumptive Campylobacter colonies from each mCCDA plate were then subcultured onto MullerHinton (MH; Difco, MD) agar containing Selective Supplement (SR117, Oxoid) and incubated microaerobically at 42°C for 48 h (Sanad et al, 2011). Pure cultures were stored at -80°C in MH broth supplemented with 30% glycerol (vol/vol) until further identification and characterization.…”
Section: Isolation Of Thermophilic Campylobacter Sppmentioning
confidence: 99%
“…A total of 98 isolates (23 C. jejuni and 75 C. coli) representing different ages, farms, and flaA clusters were tested for antimicrobial susceptibility using Sensititre Campy plates (TREK Diagnostic Systems Inc., USA) as previously described (Sanad et al, 2011(Sanad et al, , 2013. Minimum inhibitory concentrations (MICs) were determined based on Clinical and Laboratory Standards Institute (CLSI, 2012) breakpoint interpretative criteria for Campylobacteraceae.…”
Section: Antimicrobial Susceptibility Testingmentioning
confidence: 99%
“…Fewer large studies have been published for other animal sources but, as seen with chickens, the clonal complexes present vary within and among cattle herds over time, and frequently resemble those isolated from human disease isolates (Kwan et al, 2008a;Sanad et al, 2011). Some studies have identified a spatial relationship among genotypes, with isolates being more similar within rather than among farms (French et al, 2005;Kwan et al, 2008a;Rotariu et al, 2009).…”
Section: Campylobacter In Animalsmentioning
confidence: 99%